HUMAN RESOURCE DEVELOPMENT’S IMPACT ON WORK SPIRIT THROUGH EMPLOYEE ENGAGEMENT - Apri Kurniawan; Rismawati; Imam Pribadi; Muhammad Aqsa; Duriani (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
In the era of rapid technological advancements and evolving workplace dynamics, Human Resource Development (HRD) plays a critical role in enhancing employee engagement and work spirit. This study aims to investigate the impact of HRD on work spirit, with employee engagement serving as a mediating variable. The research was conducted at the Regional Secretariat of East Luwu Regency, involving 109 employees as respondents. Data were collected using a structured questionnaire and analysed using SmartPLS. The results reveal that HRD has a positive and significant impact on both employee engagement and work spirit. Additionally, the study finds that employee engagement significantly mediates the relationship between HRD and work spirit. These findings suggest that organizations should invest in comprehensive HRD programs to enhance employee engagement and, subsequently, work spirit, thereby improving overall organizational performance. The study contributes to the literature on HR management by demonstrating the crucial role of HRD in fostering a motivated and productive workforce.